The European Union and Regionalism : Conceptual and Contextual Perspectives - Cabrita, Teresa,; Idriz, Narin,; Kassoti, Eva, (International Law E-books Online, Collection 2026., 2026)
While the EU is the most emblematic Regional International Organization (RIO), the 'regional' perspective is largely absent in debates about the EU's identity and external posture. What does the 'regional' lens offer to the study of EU law? How is the regional dimension reflected in EU policymaking, and how does it impact norm production? This book offers the first critical, legal account of the EU as a RIO. It brings together scholars from different disciplines to reflect on the construction, use and misuse of the 'region' in EU law and practice and to examine how this dimension interacts with other RIOs.